Understanding Risk Factors, Clinical Presentation, and Biomarkers in Proven and Suspected Neonatal Sepsis at the Children’s Welfare Teaching Hospital, Iraq - Ali, Saja H.; Alhumairi, Rasha M; Alsudani, Aamer J. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Sepsis is recognized as the leading cause of neonatal mortality globally, yet its detection remains challenging due to inconclusive signs and symptoms. Objective: This study aimed to examine the variations in complete blood count (CBC), D-dimer, ferritin, interleukin-10, urea, and electrolyte levels among neonates with sepsis compared to healthy newborns and to identify and characterize the associated symptoms and risk factors. Methods: An observational study was conducted at the Children’s Welfare Teaching Hospital in Baghdad during the period from first of September 2023 to first of March 2024, the research involved a total of 187 neonates, including 137 neonates exhibiting clinical signs of sepsis and positive cultures, proven and suspected (case group) and 50 healthy neonates without medical condition, screened by a pediatric specialist (control group). Data collection encompassed demographic details, risk factors, and symptoms through questionnaires, followed by CBC, electrolyte, urea, D-dimer, IL-10, and ferritin assessments for all participants. Results: The total number of patients was 137, including both proven and suspected sepsis cases. The study revealed that 67 (48.91%) were male and 70 (51.14%) were female, including both early and late onset sepsis cases. The mode of delivery showed that 102 (76.12%) of 134 patients were via cesarean section (CS) and 32 (23.88%) via normal vaginal delivery (NVD). Significant differences were identified between the case and control groups in red cell distribution width (RDW), white blood cell count (WBC), and mean corpuscular volume (MCV). The lymphocyte percentage was notably lower in the case group. Hyperkalemia emerged as the most prevalent electrolyte imbalance. Additionally, urea levels were significantly elevated in the case group. Ferritin and D-dimer concentrations were markedly higher in the sepsis group, and the median IL-10 levels were significantly raised. Conclusions: The findings highlighted possible associations between NS, clinical symptoms, and maternal and neonatal risk factors. Noteworthy observations included elevated WBC, MCV, RDW, hyperkalemia, and urea levels, along with reduced lymphocyte percentages, in sepsis cases. Elevated D-dimer and ferritin levels, as well as increased IL-10 concentrations, were also significant markers. These parameters may assist in the prediction and monitoring of neonatal sepsis.